Modified Combined Approach for Distal Humerus Shaft Fracture: Anterolateral and Lateral Bimodal Approach - Lee, Tong Joo (The Korean Orthopaedic Association, 2013)
BACKGROUND: Due to the anatomical nature of the radial nerve, dissection and attainment of an adequate operative field in mid to distal humerus fracture is dangerous and limited. We devised a combined anterolateral and lateral approach that ensures protection of the radial nerve. This is achieved by performing bimodal dissection of the proximal humerus anteriorly and the distal humerus laterally. METHODS: Thirty-five consecutive patients were treated using a combined anterolateral and lateral approach for a minimum follow-up period of 24 months. We analyzed time to bony union, time to return to daily work, range of motion, elbow joint function as assessed by the Mayo elbow performance index and complications. RESULTS: Radiologic bony union was observed at 11.2 weeks (range, 8 to 20 weeks) on average. Four cases of incomplete radial nerve palsy before surgery all recovered. Time to return to work was 10.2 weeks (range, 2 to 32 weeks) on average. The average range of motion of the elbow was 3.3° (range, 0° to 10°) of extension and 135.9° (range, 125° to 145°) of flexion. There were 21 cases of excellent and 13 cases of good or better recovery, comprising over 97.1% on the Mayo elbow performance index. There were no complications of radial nerve palsy, non-union, mal-union, or infection. CONCLUSIONS: Our a modified combined anterolateral and lateral approach is a clinically effective surgical method of achieving protection of the radial nerve and securing easy and firm internal fixation.